Effect of Deer Antler Velvet on Aerobic, Anaerobic and Strength Performance - Craig Broeder; Conrad P. Earnest; Lyyn Panton; John Quindry (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2015)
Deer antler velvet (DAV) supplementation purportedly increases athletic performance; however, little data support this claim. The primary aim of our study is to examine DAV and exercise performance. We randomized 32 men (18–35 y) participating exclusively in resistance training (>4 y) to 10-weeks of randomly assigned, double blind, DAV (1350 mg, 2×/day) or placebo treatments. Primary outcomes included maximal aerobic capacity (VO2max), maximal strength (1RM; bench press and squat) and anaerobic cycling power. Secondary outcomes included comprehensive blood profiles and body composition. We used general linear models to determine changes following treatment. Eighteen participants (n = 9) completed the study with DAV participants showing significant improvements in VO2max (4.30 ±0.45 to 4.72 ±0.60 L/min, P < 0.04). The placebo and DAV groups increased bench press and squat 1RM (both, P < 0.04); yet, when expressed relative to body mass, only the DAV group showed significant bench press (4%) and squat (10%; both, P < 0.02). Neither group improved cycling performance or showed adverse changes in blood chemistries. We did observe a significant reduction in LDL-C (12%) accompanying DAV supplementation and both groups significantly reduced percent body fat (P < 0.05). Our results suggest that DAV may have ergogenic effects in men participating solely in resistance training.